Frequency of deep-seated cerebral microbleeds in patients with lobar hemorrhages and histopathological evidence for cerebral amyloid angiopathy - Huhndorf, Monika; Röcken, Christoph; Flüh, Charlotte; Weiler, Caroline; Kuhlenbäumer, Gregor; Tegeler, Nora; Schacht, Hannes; Neumann, Alexander; Margraf, Nils G.; Jensen-Kondering, Ulf (Frontiers in Neurology, 2023)
Background: Cerebral amyloid angiopathy (CAA) is a common disease and the most common cause for lobar hemorrhages in the elderly. Usually, deep seated microhemorrhages preclude the diagnosis of CAA. Here we sought to estimate the frequency of deep seated microbleeds on MRI in patients with lobar hemorrhages and histopathologic evidence for cerebral amyloid angiopathy. Additionally, we describe a cohort of patients with cortical and deep seated microbleeds on MRI and a histopathologic specimen available from lobar hematoma evacuation. Methods: Retrospective database search for histopathological specimens from lobar hematoma evacuation, additionally review of imaging findings (CT and MRI) and patient charts. Results: Between January 1st 2012 and December 31st 2020, 88 specimens from 88 patients were available. 56 specimens were excluded (no brain tissue in specimen n=4, other diagnosis n=8, no MRI n=43, no BOLD-based sequence n=1). Of the remaining 32 patients, 25 patients (78%) did not harbor deep-seated lesions on MRI of which 17 patients had histopathological features of CAA. Seven patients harbored deep seated CMB. Of these seven patients, 3 (3/20, 15%) had histopathological features of CAA. Conclusions: Around 15% of patients with histopathologically diagnosed CAA harbor deep seated microbleeds. This finding may add the discussion on how to identify patients with CAA and deep seated CMB.